THE INFLUENCE OF TECHNICAL ASSISTANCE (BIMTEK) ON THE INCREASING NUMBER OF BUMDES IN SOUTH MINAHASA, INDONESIA - Noldy Richard Supit; Grace Nathania Clara Sabandar; Nandang Rukanda (IKIP Siliwangi Bandung, 2019)
The villages currently have various economic problems such as low land tenure and relatively small business scale, some even tend to subsistence; limited access to finance and tend to be patterned 'ijon'; lack of market access and low bargaining power; less knowledgeable about good production mode; available facilities and infrastructure that have not supported production input, production process, and post production. The presence of BUMDes in this case becomes the answer to these problems, which are expected to be the motor of the village economy. However, until the end of 2017, the number of BUMDes in Indonesia is still limited to 18,446 units. This means that out of 74,958 villages in Indonesia, there are only 25% of villages that own BUMDes. This article is aimed to give a description on how Technical Assistance (BIMTEK) program on BUMDes delivered by Ministry of Villages, Underdeveloped Regions and Transmigration was able to influence the number of established BUMDes in the Region of North Minahasa, Indonesia. The two-day BIMTEK was done on 25thand 26thof September 2017 followed by field observation on the 2nduntil 4thof April 2018. This resulted on additional of 41 BUMDes in the Region of South Minahasa, which was roughly 53 % growth in six months period.